The Phenomenon of Talak to A Deceased Wife in Nagari Silantai, Sumpur Kudus District, Sijunjung District, West Sumatra Province - Paryodi Marhija Putra; Yurisman; Maulid Hariri Gani (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
Thesis entitled "The Phenomenon of Divorcing a Wife Who Has Died in Nagari Silantai, Sumpur Kudus District, Sijunjung Regency, West Sumatra Province". The aim of this research is to describe the types and implementation of talaq on deceased wives by husbands in Nagari Silantai, to be able to describe the impact on husbands if they do not perform talaq on their dead wives in Nagari Silantai, and the form of distribution of assets obtained during the marriage. The theory used in this thesis is the Phenomenological theory of Alfred Schutz. The method the author uses is a qualitative method, with data collection techniques namely observation, interviews and communication. In Nagari Silantai there are two divorce cases that are carried out on wives who have died, the first is divorce divorce, and the second, back divorce. Divorce is carried out by the husband when the wife's body is about to be washed, or even before the wife's body is buried. Talak back divorce is carried out when the wife's body leaves the house and goes to the cemetery. Talak back is a divorce that is facing away from each other, talak back is the separation of husband and wife, because they no longer have the same goal. In talak back, the husband will be taken home to his parents' house by his relatives. After the divorce divorce has been carried out, the next step is to divide the assets obtained during the marriage.